The Application Of Green Human Resource Management in Influencing The Environment Of Modern Organizations - Simatupang, Sudung; Silalahi, Marto; Putra, Hendrick Sasimtan; Putri, Debi Eka; Butarbutar, Marisi (Cita konsultindo, 2025)
Green Human Resources Management (GHRM) is a strategic approach to human resource management that integrates sustainability values and environmentally friendly practices within organizations. This study indicates that the implementation of GHRM has a positive and significant impact on the modern organizational environment by improving resource efficiency, reducing negative environmental impacts, and fostering a sustainability-oriented work culture. Furthermore, GHRM contributes to enhancing corporate image, employee loyalty, and organizational competitiveness in an era where social and ecological responsibility are highly demanded. Thus, GHRM can serve as a key pillar in building modern organizations that are adaptive, innovative, and oriented toward long-term sustainability.